1987
DOI: 10.1111/j.1525-1470.1987.tb00749.x
|View full text |Cite
|
Sign up to set email alerts
|

The Epidermal Nevus Syndrome: Case Report and Review

Abstract: A 33-year-old woman had multiple basal cell epitheliomas complicating a large, unilateral nevus sebaceus. Other unilateral epidermal nevi and a contralateral pigmentary nevoid disorder were noted on cutaneous examination. There were signs of skeletal, neurologic, and vascular involvement. This patient illustrates the unpredictable features of the epidermal nevus syndrome and the importance of close follow-up to manage attendant complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In the newborn, a uniformly tannish-brown macule without speckles may be seen, whereas the dark papules develop later [1, 8, 12, 13, 27, 31,42,43,44,45,46,48,49,50,51]. In some cases, however, the dark papules may already be noted at birth [1, 8, 14, 30]. The arrangement of papular SLN always corresponds to a checkerboard pattern although this may not be conspicuous when the lesion involves only a small area of the body.…”
Section: Papular Slnmentioning
confidence: 99%
See 2 more Smart Citations
“…In the newborn, a uniformly tannish-brown macule without speckles may be seen, whereas the dark papules develop later [1, 8, 12, 13, 27, 31,42,43,44,45,46,48,49,50,51]. In some cases, however, the dark papules may already be noted at birth [1, 8, 14, 30]. The arrangement of papular SLN always corresponds to a checkerboard pattern although this may not be conspicuous when the lesion involves only a small area of the body.…”
Section: Papular Slnmentioning
confidence: 99%
“…Papular SLN may occur as an isolated lesion [1, 4, 5, 8, 13, 14, 43, 46, 49] or as a component of phacomatosis pigmentokeratotica [1,27,28,29,30,31,32, 50, 51,55,56,57]or of SLN syndrome (table 4) [33]. Phacomatosis pigmentokeratotica has been proposed to represent an example of didymosis (twin spotting) [26].…”
Section: Papular Slnmentioning
confidence: 99%
See 1 more Smart Citation
“…1 These cases have been given various names, such as epidermal nevus syndrome, sebaceous nevus syndrome, FeuersteinMims neuroectodermal syndrome, and "nevus on a nevus." [7][8][9][10][11][12] In patient 2, a biopsy specimen obtained from the epidermal nevus showed no signs of adnexal hyperplasia. We are unable to say, however, whether such organoid differentiation is absent in all parts of the epidermal nevus.…”
Section: Commentmentioning
confidence: 99%
“…However, we recently carried out a systematic review on segmental SLN (unpublished data) and found that only 84 out of the 281 cases reported in the literature (29.9%) were part of a syndrome, and only 2 (0.7%) were associated with angiomas (and cutaneous ones) [4,5] and that in the vast majority of syndromic cases, both SLN and, if present, the associated nevus (nevus roseus or nevus sebaceus) were extensive and often involving both sides of the body.…”
mentioning
confidence: 99%